Alterations in Violinists' Practice Behaviors in Response to Differing Technical Demands in the Material. Issue 1 (July 2020) - Strietelmeier, Andrew
The pedagogical literature strongly suggests that when a musician works on a specific piece of repertoire, one should choose practice strategies tailored to the challenges presented by that material. Such a behavioral choice could represent an instantiation of focused and deliberate practice, a critical aspect of the relationship between experience and the acquisition of expertise. However, most of the literature investigating individual practice has used a single stimulus for all participants, or else has employed surveys or other proxy measures of practicing behavior. In this study, participants of three different experience levels (high school, collegiate, or professional violinists) practiced three excerpts, each featuring a different signature challenge. Results suggest that practice is highly idiosyncratic, that participants do adjust their approaches to the challenges of the material, but that individuals of differing experience levels identify remarkably similar problems within the material.